2009
DOI: 10.1111/j.1752-4571.2009.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Life‐history traits and energetic status in relation to vulnerability to angling in an experimentally selected teleost fish

Abstract: In recreational fisheries, a correlation has been established between fishing-induced selection pressures and the metabolic traits of individual fish. This study used a population of largemouth bass (Micropterus salmoides) with lines of low vulnerability fish (LVF) and high vulnerability fish (HVF) that were previously established through artificial truncation selection experiments. The main objective was to evaluate if differential vulnerability to angling was correlated with growth, energetics and nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 63 publications
(141 reference statements)
2
46
0
Order By: Relevance
“…Comparison of total lengths of offspring also revealed that HV offspring (51 mm, SD ± 6.2) were, on average, 5% smaller than LV offspring (54 mm, SD ± 5.4) in fall (Table 1), consistent with earlier findings for juvenile HV and LV largemouth bass raised under food-limited pond conditions (20). It is likely that the higher metabolic rates of HV offspring were responsible for their smaller sizes in the present experiment.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Comparison of total lengths of offspring also revealed that HV offspring (51 mm, SD ± 6.2) were, on average, 5% smaller than LV offspring (54 mm, SD ± 5.4) in fall (Table 1), consistent with earlier findings for juvenile HV and LV largemouth bass raised under food-limited pond conditions (20). It is likely that the higher metabolic rates of HV offspring were responsible for their smaller sizes in the present experiment.…”
Section: Resultssupporting
confidence: 79%
“…1B), as evidenced by the significant interaction between selection line and the covariate male size ( Table 1). The shorter duration of parental care seen for the smaller males may reflect their expected lower energy reserves coming out of winter, thereby limiting their ability to sustain parental care activities, a situation that may be particularly acute for smaller HV males because of their higher metabolic rates (19)(20)(21). The lower willingness for smaller HV males, as well as smaller and larger LV males, to provide parental care may also be due in part to their lower mating success (i.e., fewer eggs received) after spawning (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of biochemical evolution in response to indirect selection imposed by harvesting are rarer, however, and the results of the few such studies are mixed. For example, Redpath, Cooke, Arlinghaus, Wahl, and Philipp (2009) found no difference in lipid, protein or carbohydrate content between largemouth bass selected for different levels of vulnerability, despite marked changes in growth rates. In contrast, Moreno et al.…”
Section: Introductionmentioning
confidence: 99%